Implementasi Model Pembelajaran Role Play Untuk Meningkatkan Hasil Belajar PAI dan Keaktifan Belajar Siswa Kelas XI SMK Budi Utomo Perak - Ma'arif, Iin Baroroh; Rohmah, Hidayatur; Zulkurnain, Tommy (Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to determine whether the role play learning model can improve PAI learning outcomes and the learning activity of class XI TKJ ACP students at Budi Utomo Perak Vocational School. This research is classroom action research. This type of research uses descriptive qualitative and quantitative methods because this research was carried out with the aim of obtaining learning outcomes and student activity using the role play learning model. This research model refers to the Kemmis and Mc Taggart PTK model. Before using the role play learning model, student learning outcomes were below the KKM, as well as a lack of student activity and enthusiasm when participating in class learning. In this case, learning improvements are carried out. To get a solution. This research was conducted at Budi Utomo Perak Vocational School for the 2023/2024 academic year on class XI TKJ ACP students. The results of the research on students who completed cycle I were 68.42%. After making learning improvements in cycle II with a percentage of 84.21%. Meanwhile, student activity in cycle I was 69%, and cycle II was 81%. From the results of this research, it can be concluded that the use of the role play learning model can improve learning outcomes in Islamic Religious Education (PAI) subjects and the learning activity of class XI TKJ ACP SMK Budi Utomo Perak students.